Individualism vs. collectivism implications for health promotion - Pentecostes, Joy U. (1999)
This paper examines the strength and limitations o various health promotion strategies as they relate to individualism-collectivism. Individualism-collectivism is discussed in relation to the types of strategies adopted for improving health: active vs. passive measures; the strategies if education, engineering and enforcement. Findings on individualism-collectivism on the area of communication research are applied to the health promotion domain. It is hoped that the conceptual framework presented in this paper would contribute to the development of culturally appropriate health promotion interventions.
Includes bibliographical references (pages 134-135).